Mental health and service utilization among cisgender-heterosexual, sexual minority, and gender minority autistic adults - Sivathasan, Shalini; Crown, Mario J.; Rutenberg, Elizabeth; Brammell, Sarah; Thoma, Brian C.; Beck, Kelly; Conner, Caitlin M.; Mazefsky, Carla A.; Rofey, Dana (Frontiers in Psychiatry, 2026)
IntroductionAutistic people are more likely than non-autistic people to identify as sexual minority (SM) and/or gender minorities (GM), yet mental health research on these intersecting identities remains underexplored.MethodsUsing online self-report data from a large non-referred sample of 712 autistic adults (18–77 years), we compared GM, (cisgender) SM, and cisgender-heterosexual (CisHet) groups on sociodemographics, psychiatric diagnoses, service utilization, as well as current anxiety and depression symptoms. We also ran regression analyses to evaluate associations between sociodemographic characteristics and of lifetime psychiatric diagnosis.ResultsTwenty-six percent of participants endorsed having an SM identity, and 15% reported having a GM identity. Despite high rates of psychiatric diagnoses and service use in our sample overall, SM and GM participants reported higher rates of lifetime psychiatric diagnoses, outpatient service use, psychiatric hospitalizations than CisHet participants. SM and GM groups were also more likely to report current use of psychotropic medications, with the exception of antipsychotics, which were more common in the CisHet group. Moreover, regression analyses revealed that after controlling for age, educational attainment, and sex assigned at birth, sexual and gender identity variables were most strongly associated with reported diagnostic outcomes; specifically, SM and GM participants were 2–5 times more likely to report having received depression, anxiety, PTSD, and ADHD diagnoses compared with the CisHet group.ConclusionOur findings add to growing evidence that sexual and gender identities are critical variables to consider in autism research. We observed substantial differences in mental health outcomes across groups, underscoring the need for further investigation to better understand the diverse needs of autistic adults.